Dietary Behaviors of Elderly People Referred to Health Centers of Ilam, Iran - Ali Ramezankhani; Mogtasham Ghaffari; Amin Mirzaei; Sohaila Khodakarim; Parisa Taheri Tanjani; Zahra Haidaryan Zadeh (Hamadan University of Medical Sciences, 2016)
Background and Objectives: As the elderly population increases, aging diseases are also increasing. Nutritional status is the major determinants in the prevention of chronic diseases of old age. The aim of this study was to determine nutritional behaviors of the elderly in Ilam city, Iran. Materials and Methods: In this cross-sectional study, a total of 200 subjects aged over 60 years with a mean age of 61.15 ± 2.37 years were enrolled. Data were collected using a researcher-made questionnaire in two parts including demographic characteristics and nutritional behaviors. Data were analyzed using Pearson correlation, t-test and one-way ANOVA with the SPSS 19 statistical software. Results: The mean ± SD for the subjects' nutritional behaviors was 32.59±5.46 from 10 to 40 obtainable scores. The results showed that there was no significant difference between nutritional behaviors regarding gender, educational level and job status (P> 0.05). However, there was a significant positive correlation between subjects' age and nutritional behaviors (r= 0.215, P = 0.002). Also, the consumption of fruits and vegetables, grains, meats and dairy products was inadequate. Conclusions: The results of this study indicated inadequate intake of important food groups in the elderly, including fruits and vegetables, whole grains and dairy. So, planning for improving nutritional behaviors of the elderly by officials and health experts is suggested.